Traveling slippery patches produce thickness‐scale folds in ice sheets. Issue 24 (16th December 2014) - Wolovick, Michael J.; Creyts, Timothy T.; Buck, W. Roger; Bell, Robin E.
Abstract Large, complex stratigraphic folds that rise as high as 60% of the local ice thickness have been observed in ice sheets on Antarctica and Greenland. Here we show that ice deformation caused by heterogeneous and time‐variable basal sliding can produce the observed structures. We do this using a thermomechanical ice sheet model in which sliding occurs when the base approaches the melting point and slippery patches develop. These slippery patches emerge and travel downstream because of a feedback between ice deformation, vertical flow, and temperature. Our model produces the largest overturned structures, comparable to observations, when the patches move at about the ice column velocity. We conclude that the history of basal slip conditions is recorded in the ice sheet strata. These basal conditions appear to be dynamic and heterogeneous even in the slow‐flowing interior regions of large ice sheets.